The development of an instrument to measure global dimensions of maternal care in rhesus macaques (Macaca mulatta). Issue 1 (25th July 2014) - McCormack, K.; Howell, B.R.; Guzman, D.; Villongco, C.; Pears, K.; Kim, H.; Gunnar, M.R.; Sanchez, M.M.
<x xml:space="preserve">Abstract</x> One of the strongest predictors of healthy child development is the quality of maternal care. Although many measures of observation and self‐report exist in humans to assess global aspects of maternal care, such qualitative measures are lacking in nonhuman primates. In this study, we developed an instrument to measure global aspects of maternal care in rhesus monkeys, with the goal of complementing the individual behavioral data collected using a well‐established rhesus macaque ethogram during the first months postpartum. The 22 items of the instrument were adapted from human maternal sensitivity assessments and a maternal Q‐sort instrument already published for macaques. The 22 items formed four dimensions with high levels of internal reliability that represented major constructs of maternal care: (1) Sensitivity/Responsivity, (2) Protectiveness, (3) Permissiveness, and (4) Irritability. These dimensions yielded high construct validity when correlated with mother–infant frequency and duration behavior that was collected from focal observations across the first 3 postnatal months. In addition, comparisons of two groups of mothers (Maltreating vs. Competent mothers) showed significant differences across the dimensions suggesting that this instrument has strong concurrent validity, even after controlling for focal observation variables that have been previously shown to significantly differentiate these groups. Our findings suggest that this Instrument of Macaque Maternal Care has the potential to capture global aspects of the mother–infant relationship that complement individual behaviors collected through focal observations. Am. J. Primatol. 77:20–33, 2015. © 2014 Wiley Periodicals, Inc.